Epidemiological and Microbiome Associations Between Klebsiella pneumoniae and Vancomycin-Resistant Enterococcus Colonization in Intensive Care Unit Patients. (12th January 2020) - Collingwood, Abigail; Blostein, Freida; Seekatz, Anna M; Wobus, Christiane E; Woods, Robert J; Foxman, Betsy; Bachman, Michael A
Abstract: Background: Prior colonization by Klebsiella pneumoniae and vancomycin-resistant Enterococci (VRE) is associated with subsequent infection, particularly in intensive care unit (ICU) populations. Screening for VRE colonization, but not K. pneumoniae, is routinely performed in some health care systems. Identification of patient factors associated with K. pneumoniae colonization could enable infection prevention. Methods: ICU patients were screened for VRE and K. pneumoniae by rectal swab culture over 2 time periods: July–October 2014 (n = 1209) and January–May 2016 (n = 1243). Patient demographics, baseline laboratory data, comorbidities, and outcomes were analyzed. 16S rRNA gene-based analysis was performed on a subset of patients (n = 248) to identify microbiota characteristics associated with VRE and K. pneumoniae colonization. Results: K. pneumoniae colonization (17.3% of patients in the 2014 cohort, 7.3% in 2016) was significantly associated with VRE colonization in multivariable analysis ( P  = .03 in 2016; P  = .08 in 2014). VRE colonization was associated with poor underlying health, whereas K. pneumoniae colonization was associated with advanced age. The most prevalent operational taxonomic units were Escherichia coli /Shigella spp., Klebsiella, and Enterococcus, consistent with high rates of detectable K. pneumoniae and VRE by culture. Microbial community structure in noncolonized patients was significantly different from those with VRE, K. pneumoniae, or both, attributable to differences in the relative abundance of Klebsiella and Enterococcus . Conclusions: K. pneumoniae co-colonizes with VRE and is a predominant taxon in ICU patients, but colonization was not associated with significant comorbidities. Screening for K. pneumoniae and VRE simultaneously could be an efficient approach for novel infection prevention strategies.